2019
DOI: 10.1055/s-0039-1692485
|View full text |Cite
|
Sign up to set email alerts
|

Conquering the Rock—A Retrospective Single-Center Experience of the Transapical Petrosal Transtentorial (Kawase) Approach: Operative Technique and Impact on Cranial Nerve Function

Abstract: Since its description in 1985, the transapical petrosal transtentorial or Kawase approach has become a viable option of approaching lesions located in and around the apex of the petrous bone, Meckel's cave, and the anterolateral surface of the brain stem while preserving cranial nerve function. At the Brain Tumor Center, Erasmus MC, 25 patients were treated using the Kawase approach between 2004 and 2018 for various indications, including petroclival meningiomas, chondrosarcomas, pontine cavernomas, trigeminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…In our series, only 2 patients (4.1%) developed postoperative hypoacusia. Volovici et al 7 did not observe any cases of postoperative hypoacusia in their series of 25 patients who underwent operations via EAPA. Van Gompel et al 6 reported a sole patient with hypoacusia in their series of 46 patients who underwent anterior petrosectomy, and this case of hypoacusia was secondary to middle ear obliteration for the treatment of CSF fistula.…”
Section: Hearing Disturbancesmentioning
confidence: 82%
See 1 more Smart Citation
“…In our series, only 2 patients (4.1%) developed postoperative hypoacusia. Volovici et al 7 did not observe any cases of postoperative hypoacusia in their series of 25 patients who underwent operations via EAPA. Van Gompel et al 6 reported a sole patient with hypoacusia in their series of 46 patients who underwent anterior petrosectomy, and this case of hypoacusia was secondary to middle ear obliteration for the treatment of CSF fistula.…”
Section: Hearing Disturbancesmentioning
confidence: 82%
“…Studies on the morbidity of EAPA are scarce, EAPA is often grouped with other approaches related to a single pathology, 15,16 and limited publications include a large number of cases. [5][6][7] Here, we have presented a series of 49 patients who underwent operations at our institution with a focus on approach-related complications, and we have briefly outlined some technical details in order to possibly reduce these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Fukaya et al and Van Gompel et al reported a CSF leak incidence of about 4% in the ATPA [ 13 , 14 ]. In the series by Volovici et al, the risk of CSF leakage when using the ATPA was reported to be 28% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we show that we have succeeded in preventing CSF leakage by incorporating the mastoid air cell 3D simulation and multiple layer reconstruction using DuraGen ® in addition to previous proposed methods. Table S2 compares the incidence of CSF leakage and methods of CSF leakage prevention when using the ATPA between our case series and the previous literature on ATPA outcomes [ 4 , 5 , 6 , 14 , 15 , 16 , 18 ]. The incidence of CSF leakage does not show a trend of gradual improvement with age, although it is important to clarify the definition of CSF leakage.…”
Section: Discussionmentioning
confidence: 99%
“…For the whole series, the traditional skull base approach and the endoscopic endonasal approach (EEA) [11,12] were adopted for the total removal of TSs. The surgical strategy was as follows: epidural approach or subdural approach was adopted for patients with type M. The epidural approach is the standard anterior transpetrosal approach (ATPA) [13] , and the subdural approach is intradural ATPA [14,15] .…”
Section: Patient Statisticsmentioning
confidence: 99%